2D van der Waals Heterojunction of Organic and Inorganic Monolayers for High Responsivity Phototransistors - Zhao, Baolin; Gan, Ziyang; Johnson, Manuel; Najafidehaghani, Emad; Rejek, Tobias; George, Antony; Fink, Rainer; Turchanin, Andrey; Halik, Marcus (Advanced Functional Materials, 2021)
Van der Waals (vdW) heterostructures composing of organic molecules with inorganic 2D crystals open the door to fabricate various promising hybrid devices. Here, a fully ordered organic self-assembled monolayer (SAM) to construct hybrid organic–inorganic vdW heterojunction phototransistors for highly sensitive light detection is used. The heterojunctions, formed by layering MoS2 monolayer crystals onto organic [12-(benzo[b]benzo[4,5]thieno[2,3-d]thiophen-2-yl)dodecyl)]phosphonic acid SAM, are characterized by Raman and photoluminescence spectroscopy as well as Kelvin probe force microscopy. Remarkably, this vdW heterojunction transistor exhibits a superior photoresponsivity of 475 A W−1 and enhanced external quantum efficiency of 1.45 × 105%, as well as an extremely low dark photocurrent in the pA range. This work demonstrates that hybridizing SAM with 2D materials can be a promising strategy for fabricating diversified optoelectronic devices with unique properties.
CRIS-Team Scopus Importer:2021-08-06
Keywords: charge transfer; organic–inorganic hybrid; photodetection; self-assembled monolayer; transition metal dichalcogenides; van der Waals heterojunction

Buried Microphase Separation by Dynamic Interplay of Crystallization and Microphase Separation in Semicrystalline PEO-Rich PS-b-PEO Block Copolymer Thin Films - Rejek, Tobias; Schweizer, Peter; Joch, Daniel; Portilla, Luis; Spiecker, Erdmann; Halik, Marcus (Macromolecules, 2020)
The interplay between microphase separation and crystallization in the semicrystalline PS-b-PEO system is investigated in the context of solution-based thin film formation. For this end, the film morphology is studied depending on the PEO volume fraction in a broad f(vol)(PEO) range from 0.17 to 0.8. Topographical two-dimensional AFM measurements are extended to the third dimension to gain information about the vertical film structure by successive removal of the surface layer by controlled O-2 plasma etching. The depth profiling reveals a dynamic film formation process where competing microphase separation and crystallization forces create a two-layered BCP film composed of a buried microphase-separated layer featuring cylinder morphology under a fine-structured crystalline lamellae surface layer. An explanation is presented considering the thermal properties and solvent interactions. Phase-selective TiO2 nanoparticles addressing the PEO block are further used to demonstrate the accessibility of the buried microphase-separated layer and thus that we were able to extend the usable range of the phase diagram of PS-b-PEO thin films to the PEO-rich regime. Lastly, the impact of a second film-air interface is shown, which is formed in free-standing BCP membranes.
CRIS-Team WoS Importer:2020-08-07

Enhanced In Vitro Biocompatibility and Water Dispersibility of Magnetite and Cobalt Ferrite Nanoparticles Employed as ROS Formation Enhancer in Radiation Cancer Therapy - Klein, Stefanie; Kizaloglu, Melek; Portilla Berlanga, Luis; Park, Hyoungwon; Rejek, Tobias; Hümmer, Julian; Meyer, Karsten; Hock, Rainer; Distel, Luitpold; Halik, Marcus; Kryschi, Carola (Small, 2018)

Fully Printed Infrared Photodetectors from PbS Nanocrystals with Perovskite Ligands - Yousefiamin, Amirabbas; Killilea, Niall Andrew; Sytnyk, Mykhailo; Maisch, Philipp; Tam, Kwok-Kan; Egelhaaf, Hans-Joachim; Langner, Stefan; Stubhan, Tobias; Brabec, Christoph; Rejek, Tobias; Halik, Marcus; Poulsen, Katharina; et al. (ACS nano, 2019)
Colloidal nanocrystals from PbS are successfully applied in highly sensitive infrared photodetectors with various device architectures. Here, we demonstrate all-printed devices with high detectivity (similar to 10(12) cm Hz(1/2) /W) and a cut-off frequency of >3 kHz. The low material consumption (<0.3 mg per detector) and short processing time (14 s per detector) enabled by the automated printing promises extremely low device costs. To enable all-printed devices, an ink formulation was developed based on nanocrystals stabilized by perovskite-like methylammonium iodobismuthate ligands, which are dispersed in a ternary solvent. Fully inkjet printed devices based on this solvent were achieved with printed silver electrodes and a ZnO interlayer. Considerable improvements were obtained by the addition of small amounts of the polymer poly(vinylpyrrolidone) to the ink. The polymer improved the colloidal stability of the ink and its film-formation properties and thus enabled the scalable printing of single detectors and detector arrays. While photoconductors were shown here, the developed ink will certainly find application in a series of further electronic devices based on nanocrystals from a broad range of materials.
Keywords: colloidal nanocrystals; infrared detectors; inkjet printing; PbS; solution processing

Magnetite nanoparticles as efficient materials for removal of glyphosate from water - Park, Hyoungwon; May, Alexander; Portilla, Luis; Dietrich, Hanno; Münch, Friedrich; Rejek, Tobias; Sarcletti, Marco; Banspach, Leena; Zahn, Dirk; Halik, Marcus (Nature Sustainability, 2019)
Glyphosate is one of the most commonly used herbicides, but, due to its suspected toxicity, it is simultaneously the most disputed one. Its worldwide application in huge quantities may lead to water concentrations that locally exceed statutory contamination levels. Therefore, a simple toolkit is required to remove glyphosate and its major metabolite from water. Here we show a method for the magnetic remediation of glyphosate from artificial and real water samples to below the maximum permissible value or even below the analytical detection limit. The chemical structure of glyphosate enables fast and stable covalent binding on the surface of magnetite (Fe3O4) nanoparticles, which act as catchers and carriers for magnetic removal. The small size of the nanoparticles ( 20 nm diameter) provides a large active area. The glyphosate binding was analysed by infrared spectroscopy, thermogravimetric analysis and dynamic light scattering, while the remediation was investigated by liquid chromatography–mass spectrometry. Results from molecular dynamics simulations support the proposed binding mechanism. The combination of efficient remediation with inexpensive and recyclable magnetite nanoparticles suggests a simple method for the sustainable removal of glyphosate, and the concept may lead to a general approach to eliminate this class of organophosphorus compounds from water.
CRIS-Team Scopus Importer:2019-12-31

Memory Effect of Self-Assembled PS-b-PEO Block Copolymer Films with Selectively Embedded Functionalized TiO2 Nanoparticles - Kirschner, Johannes; Will, Johannes; Rejek, Tobias; Portilla Berlanga, Luis; Berlinghof, Marvin; Schweizer, Peter; Spiecker, Erdmann; Steinrück, Hans-Georg; Unruh, Tobias; Halik, Marcus (Advanced Materials Interfaces, 2017)
The memory effect in organic thin film transistors is described with a dielectric hybrid material composed of selectively localized charge trapping titania nanoparticles in a polystyrene-b-polyethyleneoxide (PS-b-PEO) diblock copolymer film. Upon solvent annealing in toluene atmosphere, the films readily form nanophase-separated features of PEO cylinders in a matrix of PS. X-ray reflectivity (XRR) investigations reveal that the TiO2 particles are selectively distributed in the top half of the hybrid layers. Applied in organic thin film transistor devices with 2-tridecyl-[1]benzothieno[3,2-b][1]benzothiophen (mono-C13-BTBT) semiconductor, the hybrid layers induce clockwise drain current hysteresis with promising memory ratio, long-term stability, and endurance. The occurrence of nonvolatile charge trapping directly relates to the hierarchically assembled nanostructure of the nanoparticles in the block copolymer since reference devices with PS homopolymers blended with TiO2 are found to be hysteresis free. Morphological characterization of the hybrid dielectric layers by atomic force microscopy and XRR experiments is presented to shed light on the internal electron density distribution. The layers are subsequently tested in capacitor stacks and transistors.

Non-substituted fused bis-tetracene based thin-film transistor with self-assembled monolayer hybrid dielectrics - Zhao, Baolin; Feofanov, Mikhail; Lungerich, Dominik; Park, Hyoungwon; Rejek, Tobias; Wittmann, Judith; Sarcletti, Marco; Amsharov, Konstantin; Halik, Marcus (Frontiers of Materials Science, 2020)
Polycyclic aromatic hydrocarbons with zigzag peripheries are high perspective candidates for organic electronics. However, large fused acenes are still poorly studied due to the tedious synthesis. Herein we report a non-substituted fused bistetracene DBATT (2.3,8.9-dibenzanthanthrene) as the semiconductor on low-voltage-driven organic thin-film transistors. The systematic studies of thin-film growth on various self-assembled monolayer (SAM) modified gate dielectrics and the electrical performances were carried out. The sub-monolayer of the semiconductor film shows larger island domains on the alkyl chain SAM. This device exhibits the hole mobility of 0.011 cm2·V−1·s−1 with a current ratio of IonIIoff above 105.
CRIS-Team Scopus Importer:2020-09-11
Keywords: contact resistance; fused bis-tetracene; organic field-effect transistor; self-assembled monolayer

Superoleophilic Magnetic Iron Oxide Nanoparticles for Effective Hydrocarbon Removal from Water - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla Berlanga, Luis; Müller, Lukas; Dietrich, Hanno; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (Advanced Functional Materials, 2019)
Various hydrocarbons are efficiently extracted from water by using a new sorbent material based on covalently functionalized magnetic nanoparticles. The functionalization of the magnetite nanoparticles with a self‐assembled monolayer of hexadecylphosphonic acid renders the nanoparticles oleophilic and the magnetic nature of magnetite allows for simple extraction of the hydrocarbon‐soaked sorbent. The sorbent material is capable of extracting single contaminants such as alkanes and aromatics and complex hydrocarbon mixtures such as crude oils in high extraction rates of up to 14 times the sorbent volume. Experimental results are explained by molecular dynamics simulations on the adsorption of single components from a hydrocarbon‐water mixture to the alkylphosphonic acid layer on the nanoparticles. The core–shell sorbent material is highly stable and therefore, reusable over several successive extraction cycles without degradation. The extraction performance is determined at different water temperatures, different water sources, and different magnetic core materials and evaluated compared to heptadecanoic acid functionalized magnetite. The new sorbent material provides the opportunity for an efficient, reliable, inexpensive, and environmental friendly removal of hydrocarbons from wate
Keywords: magnetic nanoparticles; functionalized nanoparticles; oil extraction; water remediation; phosphonic acids

Use of oleophilic magnetite nanoparticles as efficient sorbent for water contaminants - Sarcletti, Marco; Vivod, Dustin; Luchs, Tobias; Rejek, Tobias; Portilla, Luis; Hirsch, Andreas; Zahn, Dirk; Halik, Marcus (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2019)
CRIS-Team WoS Importer:2019-08-23

Wafer-Scale Organic Complementary Inverters Fabricated with Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Sarcletti, Marco; Zhao, Yuhan; Rejek, Tobias; Liu, Xinxin; Park, Hyoungwon; Strohriegl, Peter; Halik, Marcus (Advanced Electronic Materials, 2020)
Self-assembled monolayers (SAMs) of π-conjugated molecules can achieve robust charge transport by the formation of ordered 2D layers at the desired regions, which enable their application for organic integrated circuits. Here, the self-assembled monolayer field-effect transistor concept is applied as a scalable method to realize fully integrated complementary inverters by stepwise semiconductor deposition. Two-component stacked bilayer ambipolar transistors are fabricated by semiconducting self-assembled monolayers (n-SAM or p-SAM) as the bottom layer and a complementary thin-film semiconductor layer on top. The integrated complementary metal-oxide-semiconductor like (CMOS-like) inverter achieves proper logic performances. The nanometer-thin monolayers exhibit effective charge transport and their flat, homogeneous surfaces benefit the interconnected growth of the top layer. Furthermore, by controlling the solution-based and region-selective deposition of p- and n-type SAMs, fully integrated CMOS inverters are realized on wafer scale by photolithography for the first time. The CMOS inverters show a nearly 100% yield with a gain up to 48, and noise margin 3.68 V (73.6% of VDD/2). The strategy of semiconducting SAMs for digital logic gates demonstrates a reliable approach for sophisticated large-area circuits.
CRIS-Team Scopus Importer:2020-08-14
Keywords: organic complementary metal-oxide-semiconductor inverters; organic field-effect transistors; p-n heterojunction structures; self-assembled monolayers